Analisis Dampak dan Resiko Hukum Terhadap Praktik Pinjaman Online di Masa Pandemi - Iin Indriani; Nurhayati Nurhayati; Sri Utaminingsih (Rechtsregel : Jurnal Ilmu Hukum, 2021)
Technology provides many benefits for life. Its development is needed by the people of the world, it does not need the people of Indonesia. Since the beginning of 2020, the Covid-19 virus has spread to almost all countries in the world, so it requires various quick treatments by utilizing technology as an effort to deal with the pandemic situation. The Covid-19 pandemic has resulted in many Indonesian people being laid off, being laid off without a clear time limit and other economic problems. One of the uses of technology carried out by the Indonesian people during this pandemic is by using Information Technology-Based Borrowing-Lending Services. Online loans are money lending facilities by financial service providers that operate online. These credit providers are known as fintech, online loans whose funds can be immediately disbursed and without collateral are an alternative solution for people who need funds without having to apply face-to-face. The approach method used in this paper is empirical normative based on the Financial Services Authority Regulation Number 77/PJOK.01/2016 Year 2016 concerning Information Technology-Based Lending Services ("PJOK 77/2016"). In addition to being a temporary solution, online credit has impacts and risks that are often unknown and not realized by the public. The purpose of the study was to analyze the impact of the existence of online credit during the covid 19 pandemic and to analyze the legal risks of online credit that are rife in the community.